2016
DOI: 10.1074/jbc.m116.725523
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Apolipoprotein A-I as a Retinoic Acid-binding Protein in the Eye

Abstract: All-trans-retinoic acid may be an important molecular signal in the postnatal control of eye size. The goal of this study was to identify retinoic acid-binding proteins secreted by the choroid and sclera during visually guided ocular growth. Following photoaffinity labeling with all-trans-[11,12-3 H]retinoic acid, the most abundant labeled protein detected in the conditioned medium of choroid or sclera had an apparent M r of 27,000 Da. Following purification and mass spectrometry, the M r 27,000 band was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…We have also shown that choroidal expression of ApoA-1 is transcriptionally regulated by atRA, and choroidal ApoA-1 mRNA and protein synthesis are upregulated during recovery from induced myopia, suggesting the presence of a regulatory feedback mechanism to regulate atRA transport and activity [15]. We postulate that ApoA-1 functions to transport atRA from its site of synthesis by RALDH2+ cells in the proximal choroid to the sclera for the regulation of scleral ECM remodeling.…”
Section: Choroidal Retinoic Acid Synthesis and Scleral Proteoglycan Smentioning
confidence: 73%
See 3 more Smart Citations
“…We have also shown that choroidal expression of ApoA-1 is transcriptionally regulated by atRA, and choroidal ApoA-1 mRNA and protein synthesis are upregulated during recovery from induced myopia, suggesting the presence of a regulatory feedback mechanism to regulate atRA transport and activity [15]. We postulate that ApoA-1 functions to transport atRA from its site of synthesis by RALDH2+ cells in the proximal choroid to the sclera for the regulation of scleral ECM remodeling.…”
Section: Choroidal Retinoic Acid Synthesis and Scleral Proteoglycan Smentioning
confidence: 73%
“…Therefore, the requirement for carrier proteins capable of forming a soluble complex with atRA and transporting atRA to target cells is necessary to achieve high efficiency and specificity while avoiding toxicity associated with random diffusion. Mertz and Wallman [9] and our lab [15] identified a secreted protein of Mr = 27,000 that was the major atRA binding protein present in choroid and sclera conditioned medium. This Mr 27,000 protein did not correspond in size to any of the previously identified atRA binding proteins [59].…”
Section: Identification Of Apolipoprotein A-1 As a Retinoic Acid Bindmentioning
confidence: 75%
See 2 more Smart Citations
“…Six apolipoproteins were downregulated in the Zikv CZS condition compared to control. Recently, ApoA-I has been identified as an all-trans-retinoic acid-binding protein in the choroid and sclera conditioned media of chick tissue (116). Abetalipoproteinemia is an autosomal recessive disease caused by genetic mutations in the MTTP (microsomal triglyceride transfer protein) gene that result in the inability to synthesize the APOB.…”
Section: Dysregulation Of Retinoid Metabolism Has Been Associated Witmentioning
confidence: 99%